The Impact of Marketing Strategy Training on Marketing Personnel in an Effort to Achieve PT Laju Nusa Armada's Sales Target - Bayu Wega Parahita; Mohammad Ramadhani; Nindya Kartika Kusmayati (Journal of International Accounting, Taxation and Information Systems, 2024)
Failure to meet sales goals has an impact on the company's goals. goals for profits. The most fundamental issue is coming up with a strategy and a team that will give an answer for the issue. Training in marketing strategy has a fundamental objective of increasing sales and gaining an advantage over competitors with a long-term perspective. Showcasing methodologies incorporate momentary plans and long-term marketing strategies geared toward the market in order to support marketing goals and company objectives This is the reason, PT. Laju Nusa Armada, a company that provides trucking and logistic services, so that this analysis could assits the sales marketing staffs training. The outcome of a Company profit and sales performance are indicators of marketing strategy. growth. It is anticipated that this training will help explain the most recent marketing aspects. strategy to improve one's ability to come up with and analyze promoting systems in the business climate of PT. Goodbye Finapedia.